Two new species of Besleria (Gesneriaceae) from the department of Valle del Cauca, Colombia - Cortés-Ceballos, Olga Lorena; Giraldo-Rodríguez, Andrés; Torres-Gonzalez, Alba Marina (Phytotaxa, 2017)
Besleria physaloides and B. silverstoneana, two new species of Gesneriaceae from the department of Valle del Cauca, Colombia, are here described and illustrated. These two new species are similar in their vegetative morphology. However, there are differences in pubescence type and reproductive structure, especially sepals, petals, and gynoecium, between these and the other species of the genus. The two species are sympatric and grow along forest borders. The pollen morphology of the new species is also described in this study